A compatibilidade entre as competências organizacionais e as competências individuais: um estudo de caso das organizações não governamentais na cidade de João Pessoa - PB - Oliveira, Alysson André Régis de (2009)
The management of the organizacionais and individual abilities makes possible that the practical organizacionais are directed for a management more compatible effective and to the strategy of the organization. The performance of the ONGs in everybody comes growing of significant form, is of if waiting that with so great development the internal processes of management of bolder people must be each time of form to contribute in the sustentabilidade of these organizations. The study it had as objective to analyze the compatibility between the organizacionais abilities and the personal abilities of the ONGs in the city of João Person. The present research consisted of a study of multiple case applied with approach exploratóriodescription, that it aimed at to provide inside of the cognitivo period of training of knowledge, an act or effect to know the object in study, describing the characteristics of the studied phenomenon and establishing relations between 0 variable the sampling adopted in this study was defined as: theoretician, not-probabilist and for accessibility. The used sample is composed in five ONGs located in the city of João Person being represented by 70 individuals, where 58 of these act in the ONGs as popular educators and 12 of these are involved in related directive positions of the ONGs. Valley to detach that the choice of such individuals if carried through for the envolvement and linking of the same ones to the focus of the problem in study. The data had been collected through questionnaires, individual interviews half-structuralized and the comment, generating categories of 0 variable by means of the quantitative analysis and qualitative content. For the tabulação and statistical processing of the results of the research (quantitative analysis) software SPSS was used - Statistical Package will be Social Science and the electronic spread sheet Excel2003. In relation to the qualitative analysis, the commanded and organized information had been analyzed and interpreted through the use of described techniques of Analysis of Content based on the studies of Bardin. In short, the ONGs of the city of João Person is walking in direction to the compatibility between the organizacionais and individual abilities. This is proven through the changes that come happening in the form to catch and to select people for the way of the abilities and the performance of positive form by means of its organizacionais objectives, therefore exactly in an incompatibility scene the people of the ONGs possesss one high degree of envolvement, evidencing through this fact that the compatibility between the organizacionais and individual abilities, in this case in special, is not configured as a determinative factor in the envolvement/personal comprometimento of this type of organization.